The physical impacts of tourism in Zimbabwe: the state of the art - Nyahunzvi, Dzingai K. (Midlands State University, 2016)
This paper highlights and analyses the physical impacts of tourism as recorded by researchers. The main aim is to delineate the boundaries of the existing knowledge on the physical impacts of tourism and hopefully, inspire intensified research efforts. The dominant methodology adopted by most researchers on the subject has been the case study approach. However, these site specific studies though revealing, are few and confined to limited areas of the country. The impact studies are also charactérised by the absence of follow up studies and failure to take note of either indirect and induced or short term and long term impacts. The paper concludes that there is an urgent need for detailed, consistent and well coordinated research efforts from all stakeholders to ensure a symbiotic relationship between tourism and the environment in Zimbabwe